Radiation sensitization of human cancer cells in vivo by inhibiting the activity of PI3K using LY294002. - Gupta, A; Cerniglia, G; Mick, R; Ahmed, MS; Bakanauskas, V; Muschel, R; Mckenna, W (2003)
Multiple genetic alterations such as in Ras or EGFR can result in sustained signaling through PI3K. Our previous experiments have shown that resistance to radiation results from PI3K activity in cells in culture. Here we examined whether inhibition of PI3K in vivo would sensitize tumors to radiation. The human bladder cancer cell line T24 has amplified and mutated H-Ras resulting in sustained PI3K activity and phosphorylation of the downstream target of PI3K, Akt. Nude mice bearing T24 tumor cell xenografts were randomly assigned to one of four groups: control, radiation alone, the PI3K inhibitor LY294002 alone, or combined LY294002 and radiation. The LY294002 was delivered intraperitoneally to the mice. Downregulation of Akt was documented by Western blot analysis of tumor lysates. In vivo sensitization was measured using clonogenic assays or regrowth assays.A dose of 100 mg/kg of LY294002, but not 50 mg/kg, consistently eliminated the phosphorylation of Akt. This inhibition was transient, and Akt activity returned after 30 min. This dose resulted in severe respiratory depression and lethargy resolving without lethality. It is not possible to tell whether these side effects of LY294002 were mechanism-based or idiosyncratic. The PI3K inhibitor LY294002 by itself had minimal antitumor effect. The combination of LY294002 and radiation resulted in significant and synergistic reduction in clonogenicity and growth delay. Inhibition of PI3K by LY294002 can synergistically enhance radiation efficacy. This acts as a proof of principle that inhibition of the Ras to PI3K pathway could be useful clinically.